Phonetics and speech science - MacKay, Ian R. A. (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2023)
'Written in a clear, approachable way, this textbook provides an introduction to the science of phonetics: how speech sounds are produced, how we classify them, and how they are processed to allow the rapid transmission of language-based messages. Comprehensive yet accessible, it is ideal for a beginner to the field'--
Phonetics and language -- Phonetic transcription -- Anatomy and physiology of speech -- Air pressure and aerodynamics -- Consonants -- Vowels -- Sounds of North American English -- Voice, phonation, and nasality -- Airstream mechanisms: clicks, implosives, ejectives, esophageal speech -- Speech dynamics -- Suprasegmentals -- Acoustics -- Interlocutors: talkers and hearers.
Includes bibliographical references and index.
Keywords: Phonetics -- Textbooks; Speech -- Textbooks